PENCAPAIN KETUNTASAN BELAJAR SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN RECIPROCAL TEACHING DI SMA NEGERI - Pipit Permata Sari, (Pendidikan Ekonomi, 2011)
The aim of the study was to examine the use of reciprocal teaching on macro-  and micro-economic topic to achieve the students learning mastery. The study was  classroom action research. The subjects of the study were all students in class X-6 at SMA Negeri I Manyar Gresik. The data collection methods were interview, observation, test, and questionnaire. The data analysis technique was descriptive qualitative. The result of the study indicated that the use of reciprocal teaching was able to help the students to achive the learning mastery. In addition, the teachers classroom management improved, and the students activities were also good. The students also responded positively the use of the reciprocal teaching.